E-learning students' cognitive expectations in introductory physics - Mistades, Voltaire Mallari (Animo Repository, 2024)
The paper describes the use of e-learning resources - the Integrated Virtual Leaning Environment [http://ivle.dlsu.edu.ph], physlets (short Physics applets/animation), and Internet sites dedicated to Physics students-in the author's Introductory Physics classes during the last two academic years. Using a survey instruments developed and validated by the University of Maryland Physics Education Research Group, the paper also documents how students' cognitive expectations-their expectations about the learning process and the structure of knowledge-change after going through their Introductory Physics course.